Re‐evaluation of acesulfame K (E 950) as food additive - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Lourdes Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The present opinion deals with the re‐evaluation of acesulfame K (E 950) as a food additive. Acesulfame K (E 950) is the chemically manufactured compound 6‐methyl‐1,2,3‐oxathiazin‐4(3H)‐one‐2,2‐dioxide potassium salt. It is authorised for use in the European Union (EU) in accordance with Regulation (EC) No 1333/2008. The assessment involved a comprehensive review of existing authorisations, evaluations and new scientific data. Acesulfame K (E 950) was found to be stable under various conditions; at pH lower than 3 with increasing temperatures, it is degraded to a certain amount. Based on the available data, no safety concerns arise for genotoxicity of acesulfame K (E 950) and its degradation products. For the potential impurities, based on in silico data, a concern for genotoxicity was identified for 5‐chloro‐acesulfame; a maximum limit of 0.1 mg/kg, or alternatively, a request for appropriate genotoxicity data was recommended. Based on the synthesis of systematically appraised evidence of human and animal studies, the Panel concluded that there are no new studies suitable for identification of a reference point (RP) on adverse effects. Consequently, the Panel established an acceptable daily intake (ADI) of 15 mg/kg body weight (bw) per day based on the highest dose tested without adverse effects in a chronic toxicity and carcinogenicity study in rats; a study considered of moderate risk of bias and one of two key studies from the previous evaluations by the Scientific Committee on Food (SCF) and the Joint FAO/WHO Expert Committee on Food Additives (JECFA). This revised ADI replaces the ADI of 9 mg/kg bw per day established by the SCF. The Panel noted that the highest estimate of exposure to acesulfame K (E 950) was generally below the ADI in all population groups. The Panel recommended the European Commission to consider the revision of the EU specifications of acesulfame K (E 950).